Cardiac Computed Tomography in Certified German Chest Pain Units. Issue 1 (March 2016) - Breuckmann, Frank; Hochadel, Matthias; Voigtländer, Thomas; Haude, Michael; Schmitt, Claus; Münzel, Thomas; Giannitsis, Evangelos; Mudra, Harald; Heusch, Gerd; Schumacher, Burghard; Barth, Sebastian; Schuler, Gerhard; et al.
Abstract : Objective: The German Cardiac Society runs a nation-wide certification campaign for specialized chest pain units (CPUs). So far, cardiac computed tomography (CT) is not an integral part of such certification. The aim of our study was to analyze whether or not cardiac CT is nevertheless routinely used for further stratification in low-risk patients. Methods: For the time interval from January 2010 to April 2011, data were retrieved from the mandatory German CPU registry. Patients with and without cardiac CT during CPU index stay were compared. Results: Out of 5800 patients, 314 patients (5.4%) underwent cardiac CT during the index CPU stay. Unstable angina pectoris was the most common diagnosis when performing cardiac CT [34.4% vs. 17.7%; odds ratio (OR), 2.44; confidence interval (CI), 1.91–3.11; P < 0.001). Patients undergoing cardiac CT received significantly less often coronary angiography (31.8% vs. 54.8%; OR, 0.39; CI, 0.30–0.49; P < 0.001) or coronary revascularization (15.6% vs. 36.5%; OR, 0.32; CI, 0.23–0.46; P < 0.001). The use of cardiac CT did not prolong the length of stay in the CPU (20:48 vs. 20:25 h, P = 0.21). Conclusions: Cardiac CT is underrepresented within the diagnostic work up in certified CPUs in Germany, although its use reduces unnecessary invasive diagnostics. The use of cardiac CT should be reconsidered during the next update of the CPU certification criteria.